Evidence of Ice‐Rich Layered Deposits in the Medusae Fossae Formation of Mars - Thomas R. Watters; Bruce A. Campbell; Carl J. Leuschen; Gareth A. Morgan; Andrea Cicchetti; Roberto Orosei; Jeffrey J. Plaut (Geophysical Research Letters)
Abstract Subsurface reflectors in radar sounder data from the Mars Advanced Radar for Subsurface and Ionospheric Sounding instrument aboard the Mars Express spacecraft indicate significant dielectric contrasts between layers in the Martian Medusae Fossae Formation (MFF). Large density changes that create dielectric contrasts are less likely in deposits of volcanic ash, eolian sediments, and dust, and compaction models show that homogeneous fine‐grained material cannot readily account for the inferred density and dielectric constant where the deposits are more than a kilometer thick. The presence of subsurface reflectors is consistent with a multi‐layer structure of an ice‐poor cap above an ice‐rich unit analogous to the Martian Polar Layered Deposits. The volume of an ice‐rich component across the entire MFF below a 300–600 m dry cover corresponds to a global equivalent layer of water of ∼1.5 to ∼2.7 m or ∼30%–50% of the total estimated in the North Polar cap.